Risk of SARS-CoV-2 Reinfection 18 Months After Primary Infection: Population-Level Observational Study - Maria Elena Flacco; Graziella Soldato; Cecilia Acuti Martellucci; Giuseppe Di Martino; Roberto Carota; Antonio Caponetti; Lamberto Manzoli (Frontiers Media S.A., 2022)
Current data suggest that SARS-CoV-2 reinfections are rare. Uncertainties remain, however, on the duration of the natural immunity, its protection against Omicron variant, and on the impact of vaccination to reduce reinfection rates. In this retrospective cohort analysis of the entire population of an Italian region, we followed 1,293,941 subjects from the beginning of the pandemic to the current scenario of Omicron predominance (up to mid-February 2022). After an average of 277 days, we recorded 729 reinfections among 119,266 previously infected subjects (overall rate: 6.1‰), eight COVID-19-related hospitalizations (7/100,000), and two deaths. Importantly, the incidence of reinfection did not vary substantially over time: after 18-22 months from the primary infection, the reinfection rate was still 6.7‰, suggesting that protection conferred by natural immunity may last beyond 12 months. The risk of reinfection was significantly higher among females, unvaccinated subjects, and during the Omicron wave.